Sexual and Reproductive Health of Adolescent in Nepal - Shrestha, Sharmila (Journal of Karnali Academy of Health Sciences, 2018)
Every fifth person in the world i.e. around 20% of global population is adolescents and slightly more than this, in Nepal, adolescents comprise of 24 percentage. Adolescents in Nepal often face limited access to health information and services. Different factors like poverty, gender inequality, socio-economic status, social norms and tradition play crucial role indetermining adolescent’s access to sexual and reproductive health knowledge and available sexual and reproductive health services. Especially women in this context are more disadvantaged with regards to literacy, health and overall wellbeing. In Nepal adolescents comprise of 24 percentage and young people comprise of 33 percentage, which is a larger proportion to the global comparison. Though the government of Nepal has recognized adolescents and youth as under-served and vulnerable population with specific sexual and reproductive health needs, however only limited number for program has been implemented targeting these age groups.